2004
DOI: 10.1037/0022-006x.72.5.747
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Examination of Male College Students' Perpetration of Sexual Assault.

Abstract: Self-administered surveys were completed by 197 men in college at 2 time points, 1 year apart. Men who committed sexual assault at multiple time points (repeat assaulters) had the most extreme scores on measures of hostility toward women, past sexual experiences, drinking in sexual situations, and adolescent delinquency. Nonassaulters had the least extreme scores and men who committed sexual assault at only 1 time point had scores that tended to fall in between. Repeat assaulters also expressed significantly l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
338
6
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 313 publications
(375 citation statements)
references
References 65 publications
30
338
6
1
Order By: Relevance
“…The use of alcohol among college students has been consistently linked to experiences of sexual assault (Abbey, 2002;Mouilso et al, 2012;Perkins, 2002), and gender continues to play an integral role in this association (Abbey & McAuslan, 2004;Fisher et al, 2000). Abbey, Ross, McDuffie, and McAuslan (1996) found that alcohol consumption on the part of either the perpetrator or the victim was involved in 46% of the reported cases of sexual assault.…”
Section: Associations Between Drinking Behavior Alcohol Expectancy mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of alcohol among college students has been consistently linked to experiences of sexual assault (Abbey, 2002;Mouilso et al, 2012;Perkins, 2002), and gender continues to play an integral role in this association (Abbey & McAuslan, 2004;Fisher et al, 2000). Abbey, Ross, McDuffie, and McAuslan (1996) found that alcohol consumption on the part of either the perpetrator or the victim was involved in 46% of the reported cases of sexual assault.…”
Section: Associations Between Drinking Behavior Alcohol Expectancy mentioning
confidence: 99%
“…Moreover, approximately 25% to 30% of college women have experienced some form of sexual victimization that is related to problem drinking behaviors (Brahms, Ahl, Reed, & Amaro, 2011;Lawyer, Resnick, Bakanic, Burkett, & Kilpatrick, 2010;Lindgren, Neighbors, Blayney, Mullins, & Kaysen, 2012). Although the majority of research emphasizes the dichotomy of men as perpetrators (Abbey & McAuslan, 2004;Wells et al, 2014) and women as victims (Fisher, Cullen, & Turner, 2000), as many as 14% of college men have experienced some form of sexual assault as an adult (Aosved, Long, & Voller, 2011). Experiences of sexual assault among college students can range from sexually coercive tactics (e.g., threatening to disclose negative information about the person; Tyler, Hoyt, & Whitbeck, 1998) to attempted and completed rape (Fisher et al, 2000).…”
mentioning
confidence: 99%
“…Sexual assault typically occurs in dating and party situations in which alcohol consumption is common (Abbey, 2002;Testa, 2002). College student perpetrators report drinking significantly more alcohol in dating and consensual sexual situations than do nonperpetrators (Abbey & McAuslan, 2004;Abbey et al, 1998).…”
Section: Confluence Model Of Sexual Assault Perpetrationmentioning
confidence: 99%
“…For example, some research has shown an association between responses to rape-myth acceptance scales (e.g., "When women talk and act sexy, they are inviting rape"), which address misperceived justification of rape and of sexual assault perpetration (Carr and VanDeusen, 2004;Zawacki et al, 2003). Research with civilian samples has also shown an association between responses to measures of hostility toward women (e.g., "Sometimes women bother me by just being around") and sexual assault perpetration (Abbey and McAuslan, 2004;Hall et al, 2000). Other attitudinal measures that appear to be somewhat associated with sexual assault perpetration include beliefs in traditional gender roles (e.g., "It is ridiculous for a woman to run a train and a man to sew clothes" [Abbey, McAuslan, and Ross, 1998]) and hypermasculinity or hostile masculinity (e.g., "I know feminists want to be like men because men are better than women" [Malamuth et al, 1995]).…”
Section: Sexual Assault Screening Toolsmentioning
confidence: 99%
“…Studies examining criterion-related validity may use predictive methodology, involving data collection at different times, or concurrent methodology, involving data collection at the same time. Although no assessment is without limitations (e.g., see Hall, 1990), criterion-related validity assessments that may be considered include a prospective study involving Air Force personnel or applicants (e.g., Thompson et al, 2011), a longitudinal study involving Air Force personnel or applicants (e.g., Abbey and McAuslan, 2004), and examination of the association between responses of Air Force applicants or personnel to these measures and their responses about previous sexual assault behavior or their responses about the extent to which they would conduct sexual assault if there were no chance of being caught (e.g., see Drieschner and Lange, 1999). This assessment may therefore entail examining the association of scores on an integrity test administered at one time with later behavior, or it may involve examining the associations between responses to assessments that are administered at the same time.…”
Section: Use Well-validated Measures To Select Individualsmentioning
confidence: 99%